Cosmogenic evidence for limited local LGM glacial expansion, Denton Hills, Antarctica. (15th December 2017) - Joy, Kurt; Fink, David; Storey, Bryan; De Pascale, Gregory P.; Quigley, Mark; Fujioka, Toshiyuki
Abstract: The geomorphology of the Denton Hills provides insight into the timing and magnitude of glacial retreats in a region of Antarctica isolated from the influence of the East Antarctic ice sheet. We present 26 Beryllium-10 surface exposure ages from a variety of glacial and lacustrine features in the Garwood and Miers valleys to document the glacial history of the area from 10 to 286 ka. Our data show that the cold-based Miers, Joyce and Garwood glaciers retreated little since their maximum positions at 37.2 ± 6.9 (1σ n = 4), 35.1 ± 1.5 (1σ, n = 3) and 35.6 ± 10.1 (1σ, n = 6) ka respectively. The similar timing of advance of all three glaciers and the lack of a significant glacial expansion during the global LGM suggests a local LGM for the Denton Hills between ca. 26 and 51 ka, with a mean age of 36.0 ± 7.5 (1σ, n = 13) ka. A second cohort of exposure ages provides constraints to the behaviour of Glacial Lake Trowbridge that formerly occupied Miers Valley in the late Pleistocene. These data show active modification of the landscape from ∼20 ka until the withdrawal of ice from the valley mouths, and deposition of Ross Sea Drift, at 10–14 ka. Highlights: 26 exposure ages from the Denton Hills, Antarctica give ages from 10 to 286 ka. Age estimates for the local Denton Hills LGM range from 26 to 51 ka with a preferred mean age of 36 ± 8 ka. Terminal moraines are at most 100 m from the modern ice margin. The Ross Sea Drift was deposited in the valley mouths when West Antarctic ice thinned at ∼10–14 ka.